2014
DOI: 10.1007/s00261-014-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative apparent diffusion coefficient (ADC) values as an imaging biomarker for fibrosis in pediatric Crohn’s disease: preliminary experience

Abstract: Quantitative ADC measures of transmural fibrosis are lower compared to the reported values of inflammation in Crohn's disease. To our knowledge, this is the first pediatric pilot study to investigate the correlation of quantitative DWI with histology of surgical specimens in pediatric patients with Crohn's disease. Our results are comparable to a recently published study in adult Crohn's patients showing a significant correlation between a decrease in ADC values and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 18 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Oto et al 12 in a study of 18 patients reported ADC values (calculated by monoexponential signal decay) were significantly different in inflamed vs non-inflamed terminal ileum. Kovanlikaya et al 22 reported on a small cohort of five patients who underwent surgical resection. They demonstrated significant differences in ADC values between strictures and inflamed, non-stenotic segments as well as between normal and diseased bowel segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oto et al 12 in a study of 18 patients reported ADC values (calculated by monoexponential signal decay) were significantly different in inflamed vs non-inflamed terminal ileum. Kovanlikaya et al 22 reported on a small cohort of five patients who underwent surgical resection. They demonstrated significant differences in ADC values between strictures and inflamed, non-stenotic segments as well as between normal and diseased bowel segments.…”
Section: Discussionmentioning
confidence: 99%
“…For quantification of DWI parameters, monoexponential apparent diffusion coefficient (ADC) parameters were generated using all five b-values, and fits of low (0, 50 and 100 s mm 22 ) and high (300 and 600 s mm 22 ) were performed to separate fast (ADC fast ) and slow (ADC slow ) diffusion components. To account for multiexponential DWI signal decay due to microcapillary perfusion, the stretched exponential model 17 was employed where the ADC (ADC SE ) and heterogeneity index (a) were quantified.…”
Section: Dynamic Contrast-enhanced and Diffusion-weighted Imaging Anamentioning
confidence: 99%
“…A study of 5 pediatric patients with CD showed that ADC values were high in normal segments, moderate in segments with acute inflammation, and low in the presence of fibrosis. 47 There was a progressive decrease in ADC values during the clinical course. A longitudinal observation of 13 pediatric patients showed that ADC values changed with disease course.…”
Section: New Techniquesmentioning
confidence: 94%
“…36 Fourth, the b-value of standard ssDWI was adapted to 500 s/mm 2 to fit the SNR limitation of MUSE-DWI at high-resolution acquisition, although the use of b-value of 500 s/mm 2 was also included in a few studies for detecting CD. 9,37,38 The reduced b-value might help maintain wall signal for small intestines that could provide clear anatomical details for disease localization, however at the expense of sacrificing lesion contrast. 34 Further comparative studies on the optimal choice of b-value for CD diagnosis are thus needed.…”
Section: Limitationsmentioning
confidence: 99%